Performance test and water quality analysis of the use of prototype domestic wastewater treatment equipment in tilapia fish farming - Vicana Pandang Ivonda; Nurhayati; Rahardjo Sinung; Rukmono Djumbuh (BIO Web of Conferences)
Performance testing and analysis of water quality produced by domestic wastewater treatment prototypes in tilapia cultivation have been carried out. The analysis was obtained from the results of laboratory observations regarding wastewater that has been filtered using prototypes of domestic wastewater treatment equipment that have been made including pH, TDS, BOD, COD and Phosphate, then observing and analysing the application of wastewater that has been treated and used as a tilapia cultivation medium. The results of the study showed that the prototype of domestic wastewater treatment equipment produced water quality values above the water quality standards, namely a pH value of 6.1, a TDS value of 67.5 mg/l, a BOD value of 10.1 mg/l, a COD value of 640 mg/l and a Phosphate value of 2.30 mg/l. After testing the quality of water produced by domestic waste treatment using a prototype, the next is to test the water used as a tilapia cultivation medium and produce an SR value of 100%, a daily growth rate of 1.59% and an FCR of 0.33 and for the cost of making it only requires a capital of Rp 1.495.000.